KRITIK SOSIAL DALAM TEKS PRODUK DAGADU DJOKDJA: SEBUAH KAJIAN SEMIOTIKA - Sri Wahyuningtyas (LP2M Universitas Sarjanawiyata Tamansiswa, 2015)
The text Dagadu Djokdja product is poetry text which has been used for an object this research. Visualizations interesting and humorous words on the text containing many meanings of social criticsm for the society. This study using the theory of a Riffaterre’s Semiotic. The technique of data analysis done with observation, that means reading the whole text Dagadu Djokdja products. Then, the text analyzed based on instrinsic unsure, continued analyze with the theory of Riffaterre’s semiotic. The results of research shows that in the text Dagadu Djokdja product are found the existence of social criticism. Started by analyzing instrinsic unsure a poem that consisting of the theme and mandate, the sound, and diction. Followed by the analyze using the theory of a Riffaterre’s semiotic through indirectness expression, the reading of heuristic and hermeunitik, matrix and models, as well as intertekstual relations (hypogram), so there are can find the meaning of the text Dagadu Djokdja product. After that, research continue by examining the social criticism contained in the text. Some of that namely criticism on politics, criticism of education, criticism of community social conditions, criticism of economics, criticism of criminality, criticism with the culture, criticism of nationalism, criticism of defense and the country security, and strong criticism on health.Keywords: criticism, social, Dagadu Djokdja